2015
DOI: 10.1016/j.drugalcdep.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Need and utility of a polyethylene glycol marker to ensure against urine falsification among heroin users

Abstract: Background Deceptive methods of falsifying urine samples are of concern for anyone who relies on accurate urine toxicology results. A novel method to combat these efforts utilizes polyethylene glycol (PEG) markers administered orally prior to providing a urine sample. By using various PEG combinations to create a tracer capsule of unique composition, each urine sample can be matched to that individual. The goal of this study was to determine the effectiveness of using the PEG marker system among active heroin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
6
0
3
Order By: Relevance
“…Though it is made clear to participants that information concerning their drug use will not affect their participation in the study nor be shared with anyone outside of research staff, it has been shown that users may misrepresent drug use, even when there are no perceived adverse consequences (Jones et al, 2015). Despite these limitations, the data are encouraging given the staggering increases in opioid overdoses across the county.…”
Section: Discussionmentioning
confidence: 99%
“…Though it is made clear to participants that information concerning their drug use will not affect their participation in the study nor be shared with anyone outside of research staff, it has been shown that users may misrepresent drug use, even when there are no perceived adverse consequences (Jones et al, 2015). Despite these limitations, the data are encouraging given the staggering increases in opioid overdoses across the county.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have addressed how bleaching and other cosmetic treatments can affect the quality of hair samples, and the degree to which analytes can be detected, although this might not be done deliberately (American Society of Addiction Medicine (ASAM), ; Martins, Yegles, Thieme, & Wennig, ; Yegles, ). Most of the emerging evidence on circumvention focused on other specimen types, such as urine and blood (Cody & Valtier, ; Dasgupta ; Jaffee et al, ; Jones et al, ). The range and sophistication of some of those evasion methods (including even the use of a fake penis which delivers warm artificial urine) lends support to the assumption that substance users will seek to evade detection on the hair analysis also.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have addressed how bleaching and other cosmetic treatments can affect the quality of hair samples, and the degree to which analytes can be detected, although this might not be done deliberately (American Society of Addiction Medicine (ASAM), 2013; Martins, Yegles, Thieme, & Wennig, 2008;Yegles, 2005). Most of the emerging evidence on circumvention focused on other specimen types, such as urine and blood (Cody & Valtier, 2001;Dasgupta 2007;Jaffee et al, 2007;Jones et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there were a few researches concerning further urine sample validity tests for urine sample of suspected substance of abuse criminal cases, including substituted, invalid, or adulterated procedures. For pre-employment/workplace drug testing of urine samples, there have been several reports concerning urine specimen validity tests for substances abuse tests [10][11][12]. The aim of this article was to clarify our findings from urine samples adulteration attempts detected from specimen validity tests results, involving the pattern adulteration; the rates of dilution, substitution, adulteration, and finally invalid samples prevalence, in cases of pre-employment/workplace and suspected drug of abuse testing for urine samples in Saudi Arabia over one years.…”
Section: Introductionmentioning
confidence: 99%